The Legitimacy of the ‘Colectivos’ and the Police in Venezuela: A Comparative Public Opinion Study - Briceno-Rosas, Roberto; Briceño-León, Roberto (Espacio Abierto, 2023)
The so-called ‘Colectivos’ are one of the most prominent and controversial non-state armed groups in Venezuela. This study aims to compare the legitimacy of Colectivos against the level of support for the police, as state armed forces, using data from a survey of a nationally representative sample of public opinion conducted in 2021. For this purpose, data from 1,200 survey respondents is analyzed considering individual-level variables such as gender, education, work status, and political alignment, as well as contextual variables of the respondents, such as state of residence and urbanization level. The study employs a multilevel regression analysis to examine the individual and contextual factors influencing attitudes towards the polices and Colectivos among the Venezuelan population. The findings reveal a substantial lack of legitimacy for both the police and Colectivos. Moreover, the study identifies a moderate positive correlation between attitudes towards the police and Colectivos, indicating that individuals who view the police negatively are more likely to hold negative views towards Colectivos as well. Regarding the individual socio-economic variables, only political alignment was found to influence perceptions of legitimacy, whereby Chavistas viewed both polices and Colectivos more positively than non-chavistas. Additionally, the analysis of territorial differences reveals variations in public opinion towards these groups across different states. The findings highlight a concerning situation for Venezuelan population about the legitimacy of state armed forces and the potential consequences of a failed state. The perception of inefficacy of state armed forces, like the police, can leave the population feeling unprotected and vulnerable. They also indicate a potential fertile ground for non-state armed forces to control and exercise violence. The authors argue that efforts should be made to restore the state’s monopoly of violence in a legitimate and effective manner, while considering the underlying political factors and geographical differences that shape public attitudes towards armed actors. By addressing these issues, steps can be taken towards fostering a sense of security and trust among the Venezuelan population.